A comparative study of prevalence‐based incidence estimation techniques with application to dementia data in Germany. (16th September 2015) - Landwehr, Sandra; Brinks, Ralph
Abstract : Dementia is becoming a major health burden, which is mainly due to the increasing life expectancy in many developed countries. To describe the disease progression of individuals, multistate models are generally appropriate tools. These models allow the individuals to move along a path consisting of a finite number of disease states. We consider a simplifying illness–death model in which the subjects progress through the states healthy, diseased and dead . We use this model to study analytic relationships between the prevalence, incidence and mortality rates of irreversible diseases that have been applied in the past. One of these approaches is a rather recently proposed technique based on an ordinary differential equation (ODE). We conduct a simulation study to compare the performance of two suggested numerical approximations of this ODE with three alternative techniques, the common goal of which is to estimate age‐specific incidence from cross‐sectional information. The quality of the estimation methods is further explored using data on dementia in Germany. In the simulation scenarios as well as in the dementia data setting, the ODE method turns out to be the predominant technique with regard to the quality of the estimation of the known incidence regimes. Copyright © 2015 John Wiley & Sons, Ltd.